Exploring Family Resilience through the Lens of Islamic Education and Law: Analysis of Divorce Trends in Banda Aceh City - Mardhiah, Ainal; Hayati, Hayati; Umur, Azmil; Saiful, Saiful; Suriana, Suriana (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The Aceh Sharia Court documented a total of 6,448 divorce cases in the year 2021. This study employs a methodology that incorporates field studies, observation sampling techniques, interviews, and document reviews. The population consists of all divorce cases recorded at the Aceh Sharia Court in 2021, totaling 6,448. For the sample, the author selected 300 divorce cases from the city of Banda Aceh using the Purposive Sampling technique. The findings indicate that 50% of divorce cases were found among couples with low educational attainment, specifically those who completed elementary school, junior high school, high school, S1, and D3, accounting for 24%. In contrast, only 2% of divorces involved couples with S2 degrees, suggesting that a minimal portion of divorces occurred among those with higher education levels. No divorces occurred among doctoral and professor couples in Banda Aceh City. In 2021, Banda Aceh recorded a total of 300 divorce cases. The primary reason for the divorce stemmed from persistent disagreements. The findings of this study indicate that education significantly influences family resilience; specifically, a higher level of education correlates with a lower divorce rate, while a lower level of education is associated with a higher divorce rate.